Analysis of the Level of Teachers’ Religious Tolerance Attitudes at SMP Negeri 02 Somagede Banyumas - Fakih Hamdani; Munasib Munasib; Kuntarto Kuntarto; Nurchamidah Nurchamidah (Universitas Muhammadiyah Mataram, 2026)
Religious tolerance is one of the fundamental values that supports social harmony in multicultural societies and plays a crucial role in creating inclusive educational environments. Teachers, as key agents in education, are expected to demonstrate tolerant attitudes that promote respect for religious diversity among students. However, empirical studies quantitatively mapping teachers' religious tolerance at the public junior high school level remain limited. Therefore, this study aimed to analyze the level and distribution of teachers' religious tolerance at SMP Negeri 2 Somagede. This study employed a quantitative descriptive design involving 17 teachers selected through total sampling. Data were collected using a religious tolerance questionnaire consisting of 26 valid items across six dimensions. The instrument demonstrated excellent reliability with a Cronbach's Alpha coefficient of 0.961. Data were analyzed using descriptive statistics with IBM SPSS Statistics, while respondents' scores were categorized based on the Ideal Mean (Mi) and Ideal Standard Deviation (SDi) approach proposed by Azwar (2021). The results showed that teachers' religious tolerance was generally high, with a mean score of 116.65 (SD = 12.84). Based on the categorization results, 94.1% of teachers were classified in the high category and 5.9% in the moderate category, while none were classified in the low category. Among the six dimensions, Interreligious Collaboration achieved the highest mean per-item score (M = 4.68), whereas Openness to Interreligious Interaction and Dialogue obtained the lowest (M = 4.27), although both remained within the high category. These findings provide an empirical baseline for evaluating and strengthening school-based religious moderation and multicultural education programs in public junior high schools.